2009
DOI: 10.1200/jco.2008.18.9670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Adenovirus-p53 Combined With Radiotherapy on Long-Term Prognosis of Advanced Nasopharyngeal Carcinoma

Abstract: In patients with NPC, rAd-p53 was safe and biologically active. Our results indicated that rAd-p53 improves radiotherapeutic tumor control and survival rate in patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 16 publications
1
80
0
Order By: Relevance
“…This high efficiency in inducing apoptosis results from the enhanced localization of the p53 codon 72 Arg/Arg genotype to mitochondria (Dumont et al, 2003). Previous clinical studies indicated that p53 codon 72 variants were associated with the clinical outcome of NPC (Alajez et al, 2009;Pan et al, 2009;Xie et al, 2013). Xie et al (2013) reported that the p53 codon 72 Pro/Pro genotype may be an effective independent prognostic marker for better outcome in patients with locoregional NPC, and positive protein expression and local regional lymph node metastasis can predict the progression of NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high efficiency in inducing apoptosis results from the enhanced localization of the p53 codon 72 Arg/Arg genotype to mitochondria (Dumont et al, 2003). Previous clinical studies indicated that p53 codon 72 variants were associated with the clinical outcome of NPC (Alajez et al, 2009;Pan et al, 2009;Xie et al, 2013). Xie et al (2013) reported that the p53 codon 72 Pro/Pro genotype may be an effective independent prognostic marker for better outcome in patients with locoregional NPC, and positive protein expression and local regional lymph node metastasis can predict the progression of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al (2013) reported that the p53 codon 72 Pro/Pro genotype may be an effective independent prognostic marker for better outcome in patients with locoregional NPC, and positive protein expression and local regional lymph node metastasis can predict the progression of NPC. Pan et al (2009) reported that variants in p53 improved radiotherapeutic tumor control survival rate in patients with NPC. However, the results are inconsistent (Ho et al, 2001;Agaoglu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Early clinical trials have demonstrated the safety of this approach, and oncolytic viruses are now being combined with chemotherapy in various multimodal approaches of chemovirotherapy. 6 Particularly, for the treatment of advanced and/or metastasized HNSCC, Phase III clinical trials are going on using different oncolytics, which include vectors based on herpes simplex virus, adenovirus and reovirus in combination with platinum and/or taxane.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy of rAd-p53 and radiation has demonstrated good efficacy for the treatment of multiple tumors. It has also been approved as a treatment model for certain head and neck malignancies, including nasopharyngeal carcinoma (11). Previous studies have revealed that the peak time for wt-p53 expression following Gendicine treatment was 48-72 h after transfection (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%